2019
DOI: 10.3390/ijerph16050877
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Rural-To-Urban Migration, Influencing Factors and Development Framework: A Case Study of Sihe Village of Gansu, China

Abstract: Farmers are the major participants in rural development process and their willingness to settle in urban areas directly affects the implementation of rural revitalization strategy. Based on Ostrom’s institutional analysis and development (IAD) framework, we analyzed farmers’ willingness to settle in urban areas and its influencing factors by binary Logistic regression and cluster analysis of survey data of 190 rural households in Sihe village of Gansu Province of China. The results show that: (1) In Sihe villa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…About 62% of farmers migrated from one place to other with their herd in the search of fodder and water. During floods some were forced to migrate for their own and animals’ survival [9,58].…”
Section: Estimated Resultsmentioning
confidence: 99%
“…About 62% of farmers migrated from one place to other with their herd in the search of fodder and water. During floods some were forced to migrate for their own and animals’ survival [9,58].…”
Section: Estimated Resultsmentioning
confidence: 99%
“…We have not seen similar findings reported in other studies though. In a recent study of farmers' rural-to-urban migration intention, Ma, Chen, Che, and Fang (2019) reported that compared with farmers with income from both agricultural and nonagricultural productions, farmers relying on agricultural production for livelihood were less motivated to move to and settle in urban areas. With relatively stable compensation on top of their income from agricultural production, village cadres are also less willing to leave the village.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Related explorations on population migration have been concerned as hotspots since the 1990s. A larger body of researches have been conducted, such as the labor market performance, social and physical status of migration [5][6][7], the causes of migration flow [8][9][10], the consequent impacts of migration [11][12][13], the changing migration policies [14][15][16], the classification research of population migration [17,18], the spatial pattern of population migration [19], etc. These researches have been conducted mainly based on three kinds of data: national censuses data, regional field survey data, and cyber big data.…”
Section: Introductionmentioning
confidence: 99%